Melatonin downregulates the increased hepatic alpha-fetoprotein expression and restores pancreatic beta cells in a streptozotocin-induced diabetic rat model: a clinical, biochemical, immunohistochemical, and descriptive histopathological study - Alsharif, Khalaf F.; Hamad, Asmaa A.; Alblihd, Mohamed A.; Ali, Fatma Abo Zakaib; Mohammed, Sherine Ahmed; Theyab, Abdulrahman; Al-Amer, Osama M.; Almuqati, Malik Saad; Almalki, Abdulraheem Ali; Albarakati, Alaa Jameel A.; Alzahrani, Khalid J.; Albrakati, Ashraf; et al. (Frontiers in Veterinary Science, 2023)
Background Diabetes mellitus (DM) is a chronic metabolic disorder. Hepatopathy is one of the serious effects of DM Melatonin (MT) is a potent endogenous antioxidant that can control insulin output. However, little information is available about the potential association between melatonin and hepatic alpha-fetoprotein expression in diabetes. Objective This study was conducted to assess the influence of MT on diabetes-related hepatic injuries and to determine how β-cells of the pancreas in diabetic rats respond to MT administration. Materials and methods Forty rats were assigned to four groups at random (ten animals per group). Group I served as a normal control group. Group II was induced with DM, and a single dose of freshly prepared streptozotocin (45 mg/kg body weight) was intraperitoneally injected. In Group III, rats received 10 mg/kg/day of intraperitoneal melatonin (IP MT) intraperitoneally over a period of 4 weeks. In Group IV (DM + MT), following the induction of diabetes, rats received MT (the same as in Group III). Fasting blood sugar, glycosylated hemoglobin (HbA1c), and serum insulin levels were assessed at the end of the experimental period. Serum liver function tests were performed. The pancreas and liver were examined histopathologically and immunohistochemically for insulin and alpha-fetoprotein (AFP) antibodies, respectively. Results MT was found to significantly modulate the raised blood glucose, HbA1c, and insulin levels induced by diabetes, as well as the decreased alanine aminotransferase (ALT) and aspartate aminotransferase (AST). Furthermore, MT attenuated diabetic degenerative changes in the pancreas and the hepatic histological structure, increased the β-cell percentage area, and decreased AFP expression in the liver tissue. It attenuated diabetes-induced hepatic injury by restoring pancreatic β-cells; its antioxidant effect also reduced hepatocyte injury. Conclusion Collectively, the present study confirmed the potential benefits of MT in downregulating the increased hepatic alpha-fetoprotein expression and in restoring pancreatic β-cells in a streptozotocin-induced diabetic rat model, suggesting its promising role in the treatment of diabetes.